Holistic simulation of geotechnical installation processes : theoretical results and applications - Triantafyllidis, Theodoros (Lecture notes in applied and computational mechanics ;, 2017)
This book provides recent developments and improvements in the modeling as well as application examples and is a complementary work to the previous Lecture Notes Vols. 77 and 80. It summarizes the fundamental work from scientists dealing with the development of constitutive models for soils, especially cyclic loading with special attention to the numerical implementation. In this volume the neo-hypoplasticity and the ISA (intergranular strain anisotropy) model in their extended version are presented. Furthermore, new contact elements with non-linear constitutive material laws and examples for their applications are given. Comparisons between the experimental and the numerical results show the effectiveness and the drawbacks and provide a useful and comprehensive pool for all the constitutive model developers and scientists in geotechnical engineering, who like to prove the soundness of new approaches.